(untitled) - Tomasi, Wayne (New Jersey, 2005)
Written to introduce readers to the fundamental concepts of electronic communications systems, data systems, and networks, this book provides extensive coverage of a wide range of data communications and networking issues while offering preliminary information on basic electronic communications and telecommunications systems. Topics explored include wireless and wireline telecommunications systems, basic data communications networks and systems, local area networks, internetworks, and the Internet including TCP/IP protocol suite. For professionals with a career or interest in electronic communications, data communications, and/or networking, as well as ECT, EET, and CET technologists.
Keywords: Data transmission systems,Computer networks